Effects of gill abrasion and experimental infection with Tenacibaculum maritimum on the respiratory physiology of Atlantic salmon Salmo salar affected by amoebic gill disease - Powell, MD; Harris, JO; Carson, J; Hill, JV (2005)
The effects of gill abrasion and experimental infection with Tenacibaculum maritimum were assessed in Atlantic salmon Salmo salar with underlying amoebic gill disease. The respiratory and acid-base parameters arterial oxygen tension (P aO 2), arterial whole blood oxygen content (C aO 2), arterial pH (pH a), haematocrit and haemoglobin concentrations were measured at intervals over a 48 h recovery period following surgical cannulation of the dorsal aorta. Mortality rates over the recovery period were variable, with gill abrasion and inoculation with T. maritimum causing the highest initial mortality rate and unabraded, uninoculated controls showing the lowest overall mortality rate. Fish with abraded gills tended to show reduced P aO 2 and lower C aO 2 compared with unabraded fish. Infection with T. maritimum had no effect on P aO 2 or C aO 2. All fish showed an initial alkalosis at 24 h post-surgery/inoculation which was more pronounced in fish inoculated with T. maritimum. There were no significant effects of gill abrasion or infection upon the ratio of oxygen specifically bound to haemoglobin or mean cellular haemoglobin concentration. Histologically, 48 h following surgery, abraded gills showed multifocal hyperplastic lesions with pronounced branchial congestion and telangiectasis, and those inoculated with T. maritimum exhibited focal areas of branchial necrosis and erosion associated with filamentous bacterial mats. All fish examined showed signs of amoebic gill disease with multifocal hyperplastic and spongious lesions with parasome-containing amoeba associated with the gill epithelium. The results suggest that respiratory compromise occurred as a consequence of gill abrasion rather than infection with T. maritimum. Â© Inter-Research 2005.